Staff experience and attitudes towards technology-enhanced learning initiatives in one Faculty of Health and Life Sciences - Peter Reed (Association for Learning Technology, 2014)
Further to earlier work carried out by the student union (SU) along with strategic discussions regarding technology-enhanced learning (TEL), this research aimed to identify the attitudes and experience of teaching staff in relation to specific uses of technology in learning and teaching. Data obtained through an online questionnaire (n=100) suggest that teaching staff are generally agreeable to the need for consistency in the virtual learning environment and identify specific criteria to be included within 'minimum standards'; have some experience and interest in solutions to enable online submission, marking and feedback; and whilst there is more resistance, there was still interest in the provision of recorded lectures. Respondents overwhelmingly identified lack of time as a significant barrier to engaging with TEL, as well as other factors such as lack of skills and support.